Hubungan Jenis Pekerjaan Masyarakat DenganPengetahuan Tentang Leptospirosis Dan Penerapan PhbsDalam Pencegahan Leptospirosis Di Wilayah KerjaPuskesmas Ngemplak Kabupaten Boyolali - WAHYUNINGSIH, DWI NUR (2016)
Leptospirosis is caused by Leptospira bacteria that is found in the urine of rats. It is transmitted through open wounds or because of frequent contact with water. The endemic of leptospirosis in Boyolali is in Ngemplak Subdistric therefore the disease can be infecting at any time. This study aims to determine the relationship between the public work type with knowledge of leptospirosis and application of PHBS in the prevention of leptospirosis in Puskesmas Ngemplak Boyolali. This research uses analytic observational with cross sectional design. The population in this study is all the people who have already worked. The sampling technique uses multistage sampling and the total sample is 286 respondents. The analysis uses the Chi-square analysis, the result shows that there is a significant relationship between the type of work and knowledge of leptospirosis (p value = 0,021). There isn't a relationship between the type of work and the application PHBS (p value = 0,452). There is a relationship between knowledge and application of PHBS (p value = 0,000). It is advised to all of relevant parties to increase the frequency of dissemination and outreach in order to reduce leptospirosis at Puskesmas Ngemplak Boyolali. Key word : Work Type, Knowledge, PHBS Application, Leptospirosis